From Herd Boy to University Lecturer : an Autobiography - Hara, Handwell Yotamu, 1942- (MZUNI Press, 2019)
Handwell Yotamu Hara (*1942) was an ordinary boy from a village in Mzimba in Malawi. Though his parents were illiterate he was inspired through education and faith to become a primary school teacher and also earned a PhD from Pretoria University and later became a lecturer at Zomba Theological College and finally at Mzuzu University. This small autobiography is just one offered as part of the ongoing commitment by Mzuni Press to encourage Malawians to read meaningful books on a range of subjects reflecting their country's society and culture.